SAT0195 SYSTEMIC DISEASES ASSOCIATED WITH AUTOIMMUNE LIVER DISEASES. (June 2019) - KCHIR, hela; Cherif, Dhouha; Issaoui, Dhilel; Mtir, Maha; Kaffel, Dhia; Limaiem, Faten; Maamouri, Nadia
Abstract : Background: Autoimmune liver diseases are considered as a group of hepatobiliary injuries mediated by abnormal immunity in subjects with genetic predisposition. It mainly includes autoimmune hepatitis, primary biliary cholangitis, primary sclerosing cholangitis and overlap syndrome. They are oftently associated with different manifestations of autoimmune systemic diseases such as systemic lupus erythematosus, CREST syndrome …. Objectives: The aim of this study was to evaluate the prevalence and the characteristics of systemic diseases associated with autoimmune hepatopathies Methods: We carried out a retrospective study from January 1996 to December 2018 including all patients with autoimmune liver diseases followed in our department: 64primary biliary cholangitis (PBC), 22 autoimmune hepatitis (AIH), 23 overlap syndrome (OS), 15 primary sclerosing cholangitis (PSC). Results: One hundred and twenty four patients were included in our study : 107 women and 17 men with an average age of 55 years [18-87 years]. An immunological disorder was found in 58 cases (48%): [28 PBC/12 AIH/12 OS/6 PSC] with a female predominance (Sex ratio (Men/Women) = 0.09). Systemic diseases included respectively: Sjögren's syndrome in 20 cases, systemic lupus erythematosus in 7 cases, rheumatoid arthritis in 5 cases, CREST syndrome in 11 cases and autoimmune thyroiditis in 2 cases. The discovery of autoimmune disorder was in most cases concomitant to the diagnosis of the autoimmune liver disease (67%). Our study showed biological assessment perturbation in 20 cases with positivity of : anti-centromere antibodies (11 cases), anti-SSA antibodies (5 cases), anti-cardiolipin antibodies (4 cases) and rheumatoid factor (5 cases) Conclusion: Our study shows a strong prevalence of systemic disease during autoimmune hepatopathies. A systematic screening for clinical and biological immune manifestations are highly recommended in those patients. Disclosure of Interests: None declared